Analisis ungkapan sarkasme dalam Bahasa Bugis: Kajian leksikologi - Khaerah, Miftahul; Hasaniyah, Nur (Aksara: Jurnal Bahasa dan Sastra, 2023)
Bugis language is one of the regional languages in Indonesia, especially in South Sulawesi. Along with the development of the era of globalization which is increasing rapidly making language also experience development, thus affecting the style of language. Language style consists of several kinds, one of which is sarcasm. This study aims to describe the form, meaning, and factors that influence the occurrence of sarcasm in Bugis language. The type of research used is qualitative. Sources of data were obtained from oral data, Bugis-Indonesian dictionaries, books, and relevant previous articles. Data collection was carried out using editing techniques (collecting and checking data), organizing (recording and presenting facts), and founding (analyzing data findings), while data analysis was carried out using Miles and Huberman's data analysis techniques, namely data reduction, data display, and withdrawal. conclusion. This study found the results that the 21 data that had been obtained and analyzed by researchers contained a form of expression of Bugis language sarcasm that was often used as a form of designation sarcasm. Then, the factor that most often influences is the joke factor because it is to liven up the atmosphere.Keywords: Expression, Sarcasm, Bugis Language